ANALISIS PENERAPAN SISTEM MANAJEMEN KESELAMATAN DAN KESEHATAN KERJA (SMK3) PADA PEMBANGUNAN GEDUNG PASAR MARDIKA KOTA AMBON - Welem Meturan; Lenora Leuhery; Henriette Dorothy Titaley (Jurusan Teknik Sipil, 2023)
Occupational Safety and Health (K3) is a science for the aticipacion recognizing, evaluation and control of hazards that arise in the workplace that can have an impact on the welfare and health of workers. The risk of falling is the highest cause of accidents. The use of adequate safety equipment such as guardrails and helmets, as well as the implementation of security procedures such as non-permanent ladders inspection and scaffolding can reduce the risk of accidents.Data analysis was used to calculate the analysis of health and work application in the project